Collagen and collagen‐chondroitin sulfate scaffolds with uniaxially aligned pores for the biomimetic, three dimensional culture of trabecular meshwork cells. Issue 4 (7th November 2016) - Osmond, Matthew; Bernier, Sarah M.; Pantcheva, Mina B.; Krebs, Melissa D.
ABSTRACT: Glaucoma is a disease in which damage to the optic nerve leads to progressive, irreversible vision loss. The intraocular pressure (IOP) is the only modifiable risk factor for glaucoma and its lowering is considered a useful strategy for preventing or slowing down the progression of glaucomatous neuropathy. Elevated intraocular pressure associated with glaucoma is due to increased aqueous humor outflow resistance, primarily through the trabecular meshwork (TM) of the eye. Current in vitro models of the trabecular meshwork are oversimplified and do not capture the organized and complex three‐dimensional nature of this tissue that consists primarily of collagen and glycoasaminoglycans. In this work, collagen and collagen‐chondroitin sulfate (CS) scaffolds were fabricated via unidirectional freezing and lyophilization to induce the formation of aligned pores. Scaffolds were characterized by scanning electron microscopy, dynamic mechanical analysis, and a chondroitin sulfate quantification assay. Scaffold characterization confirmed the formation of aligned pores, and also that the CS was leaching out of the scaffolds over time. Primary porcine trabecular meshwork (TM) cells were seeded onto the surface of scaffolds and their gene expression, proliferation, viability, migration into the scaffolds, and morphology were examined. The TM cells were viable and proliferated 2 weeks after seeding. The cells migrated down into the internal scaffold structure and their morphology reflected the topography and alignment of the scaffold structure. This work is a promising step toward the development of a three dimensional in vitro model of the TM that can be used for testing of glaucoma pharmacological agents in future experimentation and to better our understanding of the trabecular meshwork and its complex physiology. Biotechnol. Bioeng. 2017;114: 915–923. © 2016 Wiley Periodicals, Inc. Abstract : Using a uniaxial freezing technique, scaffolds are fabricated with unaxially aligned pores. The morphologies of these scaffolds are analyzed by scanning electron microscopy and the mechanical properties determined by dynamic mechanical analysis. Trabecular meshwork cells isolated from porcine eyes are cultured on the porous scaffolds and cell growth is characterized via proliferation assay, qPCR, and confocal microscopy.